Identification of HLA class I dependent immunogenic peptides from clonotypic TCRβ expressed in cutaneous T-cell lymphoma - Zeng, Jinyang; Nguyen, Xuan-Duc; Klüter, Harald; Schönhaber, Hiltrud; Song, Mingxia; Schwinn, Nicole; Schadendorf, Dirk; Goerdt, Sergij; Eichmüller, Stefan B. (International journal of cancer, 2006)
The clonotypic T-cell receptor (TCR) is a potential target antigen for specific immunotherapy of cutaneous T-cell lymphoma (CTCL). We identified T-cell epitopes from the rearranged TCR β chain of the malignant T-cell population by the “reverse immunology” approach. Peptide-specific T-cell lines were generated against predicted epitopes and tested for the recognition of tumor cells and cells transfected with the full-length DNA coding for TCRV β chain. Two peptides derived from the clonotypic TCRVβ of a HLA-A2 positive patient could induce peptide-specific T cells from peripheral blood mononuclear cells of healthy donors and the patient as assessed by IFN-γ ELISpot assay. Furthermore, the reactive CTLs efficiently recognized autologous Sézary tumor cells, as well as HLA-A2 positive 293 cells transfected with recombinant plasmid expressing the corresponding TCRVβ29 protein. Similar results were obtained in a HLA-A3+ patient for TCRVβ7-Jβ2.7. In conclusion, our experiments show that the TCR β chain harbors epitopes suitable as targets for specific vaccination which might be a promising approach for the specific immunotherapy of cutaneous T-cell lymphoma patients. © 2006 Wiley-Liss, Inc.